Azotobacter chroococcum W5 potentiates nitrogen uptake and assimilation in wheat under reduced N fertilization and tillage practices - M. Elakkya; S. M. Manu; Prashanth Babu; S. T. M. Aravindharajan; N. Nivetha; G. Andonissamy Daniel; Govindaraj Kamalam Dinesh; Chetana Aggarwal; Sangeeta Paul (Plant Physiology Reports, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Analysis of Helium Monte Carlo Data for the ISS-CREAM Instrument - A. Bagga; S. Aggarwal; Y. Amare; D. Angelaszek; D.P. Bowman; Y.C. Chen; G.H. Choi; M. Copley; L. Derome; Z.M. Dorris; L. Eraud; J.H. Han; et al. (Advances in Space Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Drivers of extreme wintertime PM 2.5 pollution levels in North Pole, Alaska: A generalized ordered logit regression analysis - Saravanan Kanagaratnam; Raghu Betha; Kaitlyn M. McKinney; Anastasia Hewitt; Lorena A. Zanandreis; Srijan Aggarwal; Dominique Pride; Sailesh N. Behera (Atmospheric Environment, 2026)

Optimizing Flood Inundation Scenarios: Perspective of Flood Damage and Relief Economics - Susanta Das; B. M. Arjun; Diganta Barman; K. K. Sarma; S. P. Aggarwal (Journal of the Indian Society of Remote Sensing, 2025)

Enhancing resilience with operational hydrometeorological-based flood early warning system in northeast India - Diganta Barman; B M Arjun; Shyam Sundar Kundu; Rekha Bharali Gogoi; Shanbor Kurbah; Anupal Baruah; Aniket Chakravorty; S P Aggarwal (Journal of Earth System Science, 2025)

Sensitivity and Specificity of Polymerase Chain Reaction in Blood and Bronchoalveolar Lavage Samples for Mucormycosis: A Bayesian Diagnostic Test Accuracy Meta-Analysis - Valliappan Muthu; Ritesh Agarwal; Sahajal Dhooria; Inderpaul Singh Sehgal; Kuruswamy Thurai Prasad; Shivaprakash M Rudramurthy; Ashutosh N. Aggarwal; Arunaloke Chakrabarti (Mycopathologia, 2025)

Serum Mannose-Binding Lectin Levels in Asthma and Allergic Bronchopulmonary Aspergillosis - Inderpaul Singh Sehgal; Hansraj Choudhary; Valliappan Muthu; Sahajal Dhooria; Kuruswamy Thurai Prasad; Shivaprakash M. Rudramurthy; Ashutosh Nath Aggarwal; Mandeep Garg; Arunaloke Chakrabarti; Ritesh Agarwal (Mycopathologia, 2025)

P30-66 EPAA review of regulatory requirements for a second (non-rodent) species in repeated-dose toxicity studies and potential 3Rs opportunities - N. Printemps; M. Aggarwal; M. Anderton; P. Bishop; F. Chanut; K. Clark; M. Corvaro; P. Deford; O. Doehr; J. Fretton; J.-C. Garcin; A. Kampkoetter; et al. (Toxicology Letters, 2025)

Signatures of Polar Vortex Weakening in the MLTI: A Review - V. L. Harvey; D. Aggarwal; E. Becker; M. Bittner; B. Funke; L. Goncharenko; J. Jia; R. Lieberman; H.-L. Liu; V. Maliniemi; A. Marchaudon; H. Nesse; et al. (Surveys in Geophysics, 2025)
This paper is a collaborative effort that originated at the International Space Science Institute Workshop on “Physical links between Weather and Climate in Space and the Lower Atmosphere” held 22–26 January 2024. Many scientists attended that workshop and contributed their expertise related to polar vortex impacts on upper atmosphere variability. This paper summarizes well-known and newly reported signatures of polar vortex weakening on mesosphere–lower-thermosphere (MLT) temperature, winds, composition, planetary waves, gravity waves, tides, and ionospheric foF2. A variety of observational and modeling results are shown and are consistent with previously published variations in the dynamical and chemical state of the MLT and ionosphere during weak vortex events. We present Superposed Epoch Analysis (SEA) of upper atmosphere diagnostics and phenomena where day 0 is the onset of major SSWs. We also present SEAs where day 0 is the onset of stratopause warmings followed by elevated stratopause events. Our goal in performing two SEAs is to test the sensitivity of 10 hPa versus 1 hPa winds to predict upper atmosphere variability. Results suggest that zonal winds and the semidiurnal migrating solar tide (SW2) in the MLT are more sensitive to zonal wind reversals at 1 hPa rather than 10 hPa. Alternatively, the non-migrating DW2 tide in the equatorial upper mesosphere is best predicted by planetary wave-1 amplitudes in the winter high-latitude upper stratosphere rather than zonal wind reversals. A notable aspect of both SEAs is extremely large event-to-event variability in all diagnostics. Thus, conclusions drawn based on any one event are less robust than those based on many events.

Impact of Terrestrial Weather on the Space Weather of the Ionosphere-Thermosphere: Initial Results from a NASA Living with a Star Focused Science Topic - J. Oberheide; D. Aggarwal; B. Bergsson; S. Chakraborty; S. Debchoudhury; M. Dhadly; F. Gasperini; L. Goncharenko; V. L. Harvey; C. Heale; P. Inchin; J. Li; et al. (Surveys in Geophysics, 2025)
The ionosphere-thermosphere (IT) is a convergence point of energy and processes that interconnect Earth’s atmosphere with space. Processes generated by terrestrial weather in the lower atmosphere (i.e., troposphere and stratosphere, altitudes less than ~ 50 km) are recognized by the scientific community as sources of variability in both the structure and composition of the IT. Exposed to persistent wave forcing from terrestrial weather sources and solar and magnetic forcing, the IT is a domain of compelling scientific inquiry that connects thermodynamics, fluid dynamics, electrodynamics and plasma physics. Predicting its space weather is of significant national interest for space situation awareness including the very low earth orbit as the new frontier of space operations. Advancing the understanding of whole atmosphere interconnections between terrestrial and space weather requires coordinated modeling and observational efforts across different spatial and temporal scales. Toward this goal, the National Aeronautics and Space Administration (NASA), through the living with a star (LWS) program, established in 2022 a focused science topic (FST) to study the problem from various angles. In this manuscript we report on the vision, goals and status of the ongoing FST “Impact of Terrestrial Weather on the Ionosphere—Thermosphere”. Initial results show bigger impacts on the IT than hitherto thought and help to more clearly define the state-of-the-art in the context of future NASA missions such as EZIE, DYNAMIC and GDC.

Phytonoses: A threat to immunocompromised humans? - Rashmi Aggarwal; Swagata Thakur; Bishnu M. Bashyal; Titiksha Aggarwal (Indian Phytopathology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Development, validation and utility of conventional and real-time PCR based marker for the detection of Bipolaris oryzae causing brown spot disease of rice - Kartar Singh; Sapna Sharma; Aditya Tyagi; Sangeeta Gupta; Bishnu M. Bashyal; M. S. Gurjar; M. S. Saharan; Manoj Choudhary; Rashmi Aggarwal (Australasian Plant Pathology, 2025)

Characterizing metabolome signature of colostrum, transition and mature milk of indigenous cows (Bos indicus) adapted to high altitude environment of Leh-Ladakh - Amarjeet; Umesh Kumar; Monika Sodhi; Dinesh Kumar; Prince Vivek; Saket K. Niranjan; Ranjit Singh Kataria; Sudarshan Kumar; Manish Sharma; Manish Tiwari; Rajeev A.K. Aggarwal; Vijay K. Bharti; et al. (Food Chemistry, 2025)

Correction: Performance of LDBio Aspergillus ICT IgM/IgG Lateral Flow Assay in Diagnosing Chronic Pulmonary Aspergillosis in Community Versus Hospital Setting - Inderpaul Singh Sehgal; Kathirvel Soundappan; Valliappan Muthu; Sahajal Dhooria; Kuruswamy Thurai Prasad; Shivaprakash M. Rudramurthy; Ashutosh Nath Aggarwal; Rajesh Raju; Mandeep Garg; Nidhi Prabhakar; Arunaloke Chakrabarti; Ritesh Agarwal (Mycopathologia, 2025)

Performance of LDBio Aspergillus ICT IgM/IgG Lateral Flow Assay in Diagnosing Chronic Pulmonary Aspergillosis in Community Versus Hospital Setting - Inderpaul Singh Sehgal; Kathirvel Soundappan; Valliappan Muthu; Sahajal Dhooria; Kuruswamy Thurai Prasad; Shivaprakash M. Rudramurthy; Ashutosh Nath Aggarwal; Rajesh Raju; Mandeep Garg; Nidhi Prabhakar; Arunaloke Chakrabarti; Ritesh Agarwal (Mycopathologia, 2025)

Sex Differences in Allergic Bronchopulmonary Aspergillosis and its Impact on Exacerbations - Ritesh Agarwal; Valliappan Muthu; Inderpaul Singh Sehgal; Kuruswamy Thurai Prasad; Sahajal Dhooria; Mandeep Garg; Ashutosh N. Aggarwal; Shivaprakash M. Rudramurthy; Arunaloke Chakrabarti (Mycopathologia, 2024)

Biochemical, Biomarker, and Behavioral Characterization of the GrnR493X Mouse Model of Frontotemporal Dementia - Denise M. Smith; Geetika Aggarwal; Michael L. Niehoff; Spencer A. Jones; Subhashis Banerjee; Susan A. Farr; Andrew D. Nguyen (Molecular Neurobiology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Low Ionosphere Density Above the Earthquake Epicentre Region of Mw 7.2, El Mayor–Cucapah Earthquake Evident from Dense CORS Data - Gopal Sharma; Karan Nayak; Rosendo Romero-Andrade; M. A. Mohammed Aslam; K. K. Sarma; S. P. Aggarwal (Journal of the Indian Society of Remote Sensing, 2024)

Bayesian Optimization-Based Inverse Finite Element Analysis for Atrioventricular Heart Valves - Colton J. Ross; Devin W. Laurence; Ankush Aggarwal; Ming-Chen Hsu; Arshid Mir; Harold M. Burkhart; Chung-Hao Lee (Annals of Biomedical Engineering, 2024)

Role of C-Reactive Protein and Erythrocyte Sedimentation Rate in the Diagnosis and Monitoring of Treatment Response in Treatment Naïve Subjects with Chronic Pulmonary Aspergillosis - Inderpaul Singh Sehgal; Sahajal Dhooria; Shivaprakash M. Rudramurthy; Kuruswamy Thurai Prasad; Valliappan Muthu; Ashutosh Nath Aggarwal; Mandeep Garg; Pulkit Rastogi; Ritesh Agarwal (Mycopathologia, 2023)

Characterization of Treatment Response Outcomes in Chronic Pulmonary Aspergillosis: CPAnet Definitions Versus the Existing Criteria - Inderpaul Singh Sehgal; Kajal Arora; Oliver A. Cornely; Helmut J. F. Salzer; Sahajal Dhooria; Kuruswamy Thurai Prasad; Mandeep Garg; Shivaprakash M. Rudramurthy; Valliappan Muthu; Ashutosh Nath Aggarwal; Arunaloke Chakrabarti; Ritesh Agarwal (Mycopathologia, 2023)

Integrative study of Permian coal-bearing horizons: biostratigraphy, palaeovegetation, and palaeoclimate in the South Karanpura Basin - Sanghamitra Pradhan; Shreerup Goswami; Neha Aggarwal; Runcie Paul Mathews; M. C. Manoj; S. Suresh K. Pillai; Siddharth Shekhar Pradhan (Environmental Geochemistry and Health, 2023)

Higher Fat Intake Within a Vegan Diet Increases Skin Carotenoid Status in Patients at Risk for Cardiovascular Disease Participating in a Culinary Medicine Randomized Crossover Trial - A. Krenek; A. Courville; S. Chung; M. Aggarwal; A. Mathews (Journal of the Academy of Nutrition and Dietetics, 2023)

Geomechanical characteristics and failure analysis of the limestone slope at Sahastradhara–Chamasari road Dehradun Uttarakhand India - Harinandan Kumar; Nirlipta Priyadarshini Nayak; Ashish Aggarwal; M. Muralidhar Singh (Innovative Infrastructure Solutions, 2023)

Hydrological-hydrodynamic nexus for predicting flood plain inundation: a case study in Pagladiya-Putimari catchment, India - Diganta Barman; Anupal Baruah; Arjun B. M; Shiv P. Aggarwal (Arabian Journal of Geosciences, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

Expeditious microwave assisted green synthesis of phosphorous doped carbon obtained from Mangifera Indica for adsorptive desulfurization of fuel - M. Christina Nilavu; B. Arunraj; Himanshu Aggarwal; N. Rajesh (Fuel, 2023)

Gangotri glacier dynamics from multi-sensor SAR and optical data - Praveen Kumar Thakur; Anukesh Krishnankutty Ambika; Sanjay M. Bisht; Alfred Stein; Anirudha Mahagaonkar; Uday Kumar; Vaibhav Garg; Varun Khajuria; Arpit Chouksey; Snehmani; Prakash Chauhan; SP Aggarwal (Advances in Space Research, 2023)

Multiple sequence alignment and phylogenetic analysis of wheat pathogens using conserved genes for identification and development of diagnostic markers - Sangeeta Gupta; Rashmi Aggarwal; Sapna Sharma; Malkhan S. Gurjar; Bishnu M. Bashyal; Mahender S. Saharan; Shweta Agarwal (Cereal Research Communications, 2022)

A transition management framework to stimulate a circular phosphorus system - Heidi M. Peterson; Lawrence A. Baker; Rimjhim M. Aggarwal; Treavor H. Boyer; Neng Iong Chan (Environment, Development and Sustainability, 2022)

Identification of aquaporins and deciphering their role under salinity stress in pomegranate (Punica granatum) - Surbhi Kumawat; Bharti Aggarwal; Nitika Rana; Rushil Mandlik; Akrity Mehra; S. M. Shivaraj; Humira Sonah; Rupesh Deshmukh (Journal of Plant Biochemistry and Biotechnology, 2021)

An Efficient Void Aware Framework for Enabling Internet of Underwater Things - Ahmad M. Khasawneh; Maryam Altalhi; Arvind Kumar; Geetika Aggarwal; Omprakash Kaiwartya; Ala’ Khalifeh; Mahmoud Ahmad Al-Khasawneh; Ala Abdulsalam Alarood (Journal of Marine Science and Engineering, 2021)
The Internet of Underwater Things (IoUT) is an emerging area in marine science and engineering. It has witnessed significant research and development attention from both academia and industries due to its growing underwater use cases in oceanographic data collection, pollution monitoring, seismic monitoring, tactical surveillance, and assisted navigation for waterway transport. Information dissemination in the underwater network environment is very critical considering network dynamism, unattainable nodes, and limited resources of the tiny IoUT devices. Existing techniques are majorly based on location-centric beacon messages, which results in higher energy consumption, and wastage of computing resources in tiny IoUT devices. Towards this end, this paper presents an efficient void aware (EVA) framework for information dissemination in IoUT environment. Network architecture is modeled considering potential void region identification in the underwater network environment. An efficient void aware (EVA) information dissemination framework is proposed focusing on detecting void network region, and intelligent void aware data forwarding. The comparative performance evaluation attests to the benefits of the proposed framework in terms of energy consumption, network lifetime, packet delivery ratio, and end-to-end delay for information dissemination in IoUT.

Alleviation of heat stress by Chlorophytum borivilianum: impact on stress markers, antioxidant, and immune status in crossbred cows - Pooja Devi; Mahendra Singh; Yallappa M. Somagond; Anjali Aggarwal (Tropical Animal Health and Production, 2021)

Fusarium head blight of wheat in India‐variability in pathogens associated and sources of resistance: an overview - Mahender Singh Saharan; H. M. Akshay Kumar; Malkhan Singh Gurjar; Rashmi Aggarwal (Indian Phytopathology, 2021)

Tilletia indica: biology, variability, detection, genomics and future perspective - Malkhan Singh Gurjar; Haritha Mohan M; Jagmohan Singh; Mahender Singh Saharan; Rashmi Aggarwal (Indian Phytopathology, 2021)

Improved methodology for the isolation of false smut pathogen Ustilaginoidea virens of rice - B. M. Bashyal; Pooja Parmar; Najam Waris Zaidi; Sunil Kumar Sunani; G. Prakash; Rashmi Aggarwal (Indian Phytopathology, 2021)

Molecular detection of Fusarium graminearum causing head blight of wheat by loop mediated isothermal amplification (LAMP) assay - S. Gupta; M. S. Saharan; M. S. Gurjar; J. Singh; B. M. Bashyal; R. Aggarwal (Indian Phytopathology, 2020)

Shoot organogenesis and assessment of clonal fidelity of regenerated plants of Ocimum tenuiflorum L.: Queen of Herbs - Diwakar Aggarwal; Nisha Neeti; M. Sudhakar Reddy; Anil Kumar (Vegetos, 2020)

Identification and expression analysis of pathogenicity-related genes in Tilletia indica inciting Karnal bunt of wheat - J. Singh; R. Aggarwal; M. S. Gurjar; S. Sharma; S. Jain; M. S. Saharan (Australasian Plant Pathology, 2020)

Environmental friendly synthesis of zinc oxide nanoparticles and estimation of its larvicidal activity against Aedes aegypti - S. M. Roopan; R. S. Mathew; S. S. Mahesh; D. Titus; K. Aggarwal; N. Bhatia; K. I. Damodharan; K. Elumalai; J. J. Samuel (International Journal of Environmental Science and Technology, 2019)

Fusarium graminearum microRNA-like RNAs and their interactions with wheat genome: a much-needed study - Lalit L. Kharbikar; Arti S. Shanware; M. S. Saharan; Shweta K. Nandanwar; P. N. Sivalingam; Malkhan S. Gurjar; Rashmi Aggarwal (Indian Phytopathology, 2019)

Common Genetic Variants Link the Abnormalities in the Gut-Brain Axis in Prematurity and Autism - Elżbieta M. Sajdel-Sulkowska; Monika Makowska-Zubrycka; Katarzyna Czarzasta; Kaja Kasarello; Vishal Aggarwal; Michał Bialy; Ewa Szczepanska-Sadowska; Agnieszka Cudnoch-Jedrzejewska (The Cerebellum, 2019)

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Metal induction of a P isolithus albus metallothionein and its potential involvement in heavy metal tolerance during mycorrhizal symbiosis - M. Sudhakara Reddy; Manpreet Kour; Sipla Aggarwal; Shanky Ahuja; Roland Marmeisse; Laurence Fraissinet‐Tachet (Environmental Microbiology, 2016)
Summary Metallothioneins ( MTs ) are small, cysteine‐rich peptides involved in intracellular sequestration of heavy metals in eukaryotes. We examined the role in metal homeostasis and detoxification of an MT from the ectomycorrhizal fungus P isolithus albus ( PaMT1 ). PaMT1 encodes a 35 amino acid‐long polypeptide, with 7 cysteine residues; most of them part of a C ‐x‐ C motif found in other known basidiomycete MTs . The expression levels of PaMT1 increased as a function of increased external C u and C d concentrations and were higher with C u than with C d. Heterologous complementation assays in metal‐sensitive yeast mutants indicated that PaMT1 encodes a polypeptide capable of conferring higher tolerance to both C u and C d. E ucalyptus tereticornis plantlets colonized with P . albus grown in the presence of C u and C d showed better growth compared with those with non‐mycorrhizal plants. Higher PaMT1 expression levels were recorded in mycorrhizal plants grown in the presence of C u and C d compared with those in control mycorrhizal plants not exposed to heavy metals. These data provide the first evidence to our knowledge that fungal MTs could protect ectomycorrhizal fungi from heavy metal stress and in turn help the plants to establish in metal‐contaminated sites.

Cognitive and institutional influences on farmers’ adaptive capacity: insights into barriers and opportunities for transformative change in central Arizona - Hallie Eakin; Abigail York; Rimjhim Aggarwal; Summer Waters; Jessica Welch; Cathy Rubiños; Skaidra Smith-Heisters; Chrissie Bausch; John M. Anderies (Regional Environmental Change, 2016)

Occurrence, identification and pathogenicity of Fusarium species associated with bakanae disease of basmati rice in India - B. M. Bashyal; Rashmi Aggarwal; Sapna Sharma; Sangeeta Gupta; Kirti Rawat; Dhiraj Singh; A. K. Singh; S. Gopala Krishnan (European Journal of Plant Pathology, 2016)

Emergence of Aggressive Population in the Bipolaris sorokiniana of Barley (Hordeum vulgare L.) Through Anastomosis - B. M. Bashyal; Ramesh Chand; Rashmi Aggarwal (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Dynamics of ultrafine particles inside a roadway tunnel - V. K. Mishra; M. L. Aggarwal; P. Berghmans; E. Frijns; L. Int Panis; K. M. Chacko (Environmental Monitoring and Assessment, 2015)

Feasibility of using a particle counter or flow-cytometer for bacterial enumeration in the assimilable organic carbon (AOC) analysis method - Srijan Aggarwal; Youchul Jeon; Raymond M. Hozalski (Biodegradation, 2015)

Genetic transformation of endo-1,4-β-glucanase (Korrigan) for cellulose enhancement in Eucalyptus tereticornis - Diwakar Aggarwal; Anil Kumar; M. Sudhakara Reddy (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Induction of Osmoadaptive Mechanisms and Modulation of Cellular Physiology Help Bacillus licheniformis Strain SSA 61 Adapt to Salt Stress - Sangeeta Paul; Chetana Aggarwal; Jyoti Kumar Thakur; G. S. Bandeppa; Md. Aslam Khan; Lauren M. Pearson; Gyorgy Babnigg; Carol S. Giometti; Andrzej Joachimiak (Current Microbiology, 2015)

Multimodel ensembles of wheat growth: many models are better than one - Pierre Martre; Daniel Wallach; Senthold Asseng; Frank Ewert; James W. Jones; Reimund P. Rötter; Kenneth J. Boote; Alex C. Ruane; Peter J. Thorburn; Davide Cammarano; Jerry L. Hatfield; Cynthia Rosenzweig; et al. (Global Change Biology, 2015)
Crop models of crop growth are increasingly used to quantify the impact of global changes due to climate or crop management. Therefore, accuracy of simulation results is a major concern. Studies with ensembles of crop models can give valuable information about model accuracy and uncertainty, but such studies are difficult to organize and have only recently begun. We report on the largest ensemble study to date, of 27 wheat models tested in four contrasting locations for their accuracy in simulating multiple crop growth and yield variables. The relative error averaged over models was 24–38% for the different end‐of‐season variables including grain yield ( GY ) and grain protein concentration ( GPC ). There was little relation between error of a model for GY or GPC and error for in‐season variables. Thus, most models did not arrive at accurate simulations of GY and GPC by accurately simulating preceding growth dynamics. Ensemble simulations, taking either the mean (e‐mean) or median (e‐median) of simulated values, gave better estimates than any individual model when all variables were considered. Compared to individual models, e‐median ranked first in simulating measured GY and third in GPC . The error of e‐mean and e‐median declined with an increasing number of ensemble members, with little decrease beyond 10 models. We conclude that multimodel ensembles can be used to create new estimators with improved accuracy and consistency in simulating growth dynamics. We argue that these results are applicable to other crop species, and hypothesize that they apply more generally to ecological system models.

Purification and characterization of a novel toxin from Bipolaris sorokiniana , causing spot blotch of wheat and analysis of variability in the pathogen - M. Jahani; R. Aggarwal; S. Gupta; S. Sharma; P. Dureja (Cereal Research Communications, 2014)

Factors affecting genetic transformation and shoot organogenesis of Bacopa monnieri (L.) Wettst - Diwakar Aggarwal; Neha Jaiswal; Anil Kumar; M. Sudhakara Reddy (Journal of Plant Biochemistry and Biotechnology, 2013)

A sensitivity study on the role of the swamps of southern Sudan in the summer climate of North Africa using a regional climate model - Modathir A. H. Zaroug; M. B. Sylla; F. Giorgi; Elfatih A. B. Eltahir; Pradeep K. Aggarwal (Theoretical and Applied Climatology, 2013)

Simulating the impacts of climate change on cotton production in India - K. B. Hebbar; M. V. Venugopalan; A. H. Prakash; P. K. Aggarwal (Climatic Change, 2013)

Erratum to: Celastrol suppresses invasion of colon and pancreatic cancer cells through the downregulation of expression of CXCR4 chemokine receptor - Vivek R. Yadav; Bokyung Sung; Sahdeo Prasad; Ramaswamy Kannappan; Sung-Gook Cho; Mingyao Liu; Madan M. Chaturvedi; Bharat B. Aggarwal (Journal of Molecular Medicine, 2013)

Permian Triassic palynofloral transition in Chintalapudi area, Godavari Graben, Andhra Pradesh, India - NEERJA JHA; M BASAVA CHARY; NEHA AGGARWAL (Journal of Earth System Science, 2012)

Factors affecting micropropagation and acclimatization of an elite clone of Eucalyptus tereticornis Sm. - Diwakar Aggarwal; Anil Kumar; Jagriti Sharma; M. Sudhakara Reddy (In Vitro Cellular & Developmental Biology - Plant, 2012)

N-acetyl-l-cysteine modulates multiple signaling pathways to rescue male germ cells from apoptosis induced by chronic hCG administration to rats - Ankur Maheshwari; M. M. Misro; Archana Aggarwal; Rajnesh K. Sharma (Apoptosis, 2012)

Marine exposure trials on two treated timbers used for fabricating catamarans - M. V. Rao; Pankaj K. Aggarwal (Journal of the Indian Academy of Wood Science, 2011)

Agrobacterium tumefaciens mediated genetic transformation of selected elite clone(s) of Eucalyptus tereticornis - Diwakar Aggarwal; Anil Kumar; M. Sudhakara Reddy (Acta Physiologiae Plantarum, 2011)

Celastrol suppresses invasion of colon and pancreatic cancer cells through the downregulation of expression of CXCR4 chemokine receptor - Vivek R. Yadav; Bokyung Sung; Sahdeo Prasad; Ramaswamy Kannappan; Sung-Gook Cho; Mingyao Liu; Madan M. Chaturvedi; Bharat B. Aggarwal (Journal of Molecular Medicine, 2010)

Shoot organogenesis in elite clones of Eucalyptus tereticornis - Diwakar Aggarwal; Anil Kumar; M. Sudhakara Reddy (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Determination of biofilm mechanical properties from tensile tests performed using a micro-cantilever method - Srijan Aggarwal; Raymond M. Hozalski (Biofouling, 2010)

Endophytic Bacteria from Ocimum sanctum and Their Yield Enhancing Capabilities - Rashmi Tiwari; Alok Kalra; M. P. Darokar; Mahesh Chandra; Nitin Aggarwal; A. K. Singh; S. P. S. Khanuja (Current Microbiology, 2010)

Induction of Oxidative Stress in Erythrocytes of Male Rats Subchronically Exposed to a Mixture of Eight Metals Found as Groundwater Contaminants in Different Parts of India - S. H. Jadhav; S. N. Sarkar; M. Aggarwal; H. C. Tripathi (Archives of Environmental Contamination and Toxicology, 2007)

Effect of low-dose omega-3 fatty acids substitution on blood pressure, hyperinsulinemia and dyslipidemia in Indians with essential hypertension: A pilot study - A. Bhise; P. V. Krishnan; R. Aggarwal; M. Gaiha; J. Bhattacharjee (Indian Journal of Clinical Biochemistry, 2005)

Increasing the efficiency of agronomy experiments in potato using INFOCROP-POTATO model - J. P. Singh; P. M. Govindakrishnan; S. S. Lal; P. K. Aggarwal (Potato Research, 2005)

Andean beans (Phaseolus vulgaris L.) with resistance to the angular leaf spot pathogen (Phaeoisariopsis griseola) in southern and eastern Africa - Vas D. Aggarwal; Marcial A. Pastor-Corrales; Rowland M. Chirwa; Robin A. Buruchara (Euphytica, 2004)

Acidification of Surface Water in Central India - Shankar G. Aggarwal; Chandra K. Chandrawanshi; Raj M. Patel; Smita Agarwal; Anand Kamavisdar; Girdhar L. Mundhara (Water, Air, & Soil Pollution, 2001)

Role of Biomolecules from human renal stone matrix on COM crystal growth - S. Aggarwal; C.D. Tandon; M. Forouzandeh; S.K. Singla; R. Kiran; R.K. Jethi (Molecular and Cellular Biochemistry, 2000)

Inhibitors of in vitro mineralization from flexor tendons of rabbits and their role in biological mineralization - C.D. Tandon; M. Forouzandeh; S. Aggarwal; R.K. Jethi (Molecular and Cellular Biochemistry, 1997)